Mathematics
jayresendez254
5

Solve each of these systems using the substitution method. Make sure to check your answers ! 2x + 3y = -4 x − 2y = 5

+0
(1) Answers
lhaelha2

X -2y = 5 X -2y +2y = 5 +2y X = 5 + 2y Plug this into first formula. 2X + 3y = -4 2 (5 + 2y) +3y = -4 10 + 4y +3y = -4 10 + 7y = -4 10 -10 + 7y = -4 -10 7y = -14 7y/7 = -14/7 y = -2 Now plug Y back into 2x + 3y = -4 2x + 3(-2) = -4 2x -6 = -4 2x -6 +6 = -4 +6 2x = 2 2x/2 = 2/2 x = 1 Check by plugging X & y values in either formula. 2(1) + 3(-2) = -4 2 -6 = -4 -4 = -4

Add answer